2022
DOI: 10.1111/pbi.13968
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Camelina neglecta, a diploid progenitor of the hexaploid oilseed Camelina sativa

Abstract: Summary Camelina neglecta is a diploid species from the genus Camelina, which includes the versatile oilseed Camelina sativa. These species are closely related to Arabidopsis thaliana and the economically important Brassica crop species, making this genus a useful platform to dissect traits of agronomic importance while providing a tool to study the evolution of polyploids. A highly contiguous chromosome‐level genome sequence of C. neglecta with an N50 size of 29.1 Mb was generated utilizing Pacific Bioscience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 100 publications
2
15
3
Order By: Relevance
“…The FLC ortholog in Camelina neglecta , a diploid progenitor of C. sativa , aligns with the winter‐type Csa . FLC.C08 , suggesting this to be the ancestral copy (Chaudhary et al., 2023) (Figure S12) . Csa.FLC.C13 could only be reconstructed from C. alyssum and showed only synonymous sequence variation compared to the reference genome.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The FLC ortholog in Camelina neglecta , a diploid progenitor of C. sativa , aligns with the winter‐type Csa . FLC.C08 , suggesting this to be the ancestral copy (Chaudhary et al., 2023) (Figure S12) . Csa.FLC.C13 could only be reconstructed from C. alyssum and showed only synonymous sequence variation compared to the reference genome.…”
Section: Discussionmentioning
confidence: 95%
“…It has previously been shown that C. sativa and its diploid progenitor C. neglecta do not appear to contain an ortholog of a key gene in the A. thaliana flowering pathway, FRIGIDA ( FRI ) (Chaudhary et al., 2023). Thus, the expression of flowering‐related genes was explored to infer whether the well‐defined pathways of A. thaliana (Teotia & Tang, 2015) were in fact good predictors for gene expression in C. sativa (Figure 5; Table S2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that C. sativa and its diploid progenitor C. neglecta do not appear to contain an ortholog of a key gene in the A. thaliana flowering pathway, FRIGIDA (FRI) (Chaudhary et al, 2022). Thus the expression of flowering-related genes was explored to infer whether the well-defined pathways of A. thaliana (Teotia and Tang, 2015) were in fact good predictors for gene expression in C. sativa (Figure 5; Table S8A).…”
Section: Pathway For Flowering In Camelinamentioning
confidence: 99%